Creative arts therapy careers - Bailey, Sally D. (PERFORM : succeeding as a creative professional, 2022)
"Creative Arts Therapy Careers is a collection of essays written by and interviews with professors of creative arts therapies and registered drama therapists, dance/movement therapists, music therapists, art therapists, poetry therapists, and expressive arts therapists. The book sheds light on the fascinating yet little-known field of the creative arts therapies - psychotherapy approaches which allow clients to use creativity and artistic expression to explore their lives, solve their problems, make meaning, and heal from their traumas. Featuring stories of educators in each of the six fields and at different stages of their career, it outlines the steps one needs to take in order to find training in one of the creative arts therapies, exploring the healing aspects of the arts, where creative arts therapists work, who they work with, and how they use the arts in therapy. Contributors to this book provide a wealth of practical information, including ways to find opportunities to work with at-risk populations in order to gain experience with the arts as healing tools; choosing the right graduate school for further study; the difference between registration, certification, and licensure; and the differences between a career in a medical, mental health, educational, correctional, or service institution. This book illuminates creative arts therapy career possibilities for undergraduate and graduate students studying acting, directing, playwriting, creative writing, visual arts, theatre design, dance, and music. It is also an excellent resource for instructors offering a course to prepare arts students for the professional world"--